THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE ON ORGANIZATIONAL COMMITMENT, EMPLOYEE ENGAGEMENT, AND EMPLOYEE PERFORMANCE PT. PLN (PERSERO) UP3 BUKITTINGGI - Avin Aferi; Harif Amali; Hendra Lukito (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
In a company, many factors support the sustainability of the company, especially in the era of globalization which increases competition between companies. To be able to survive in the current era of global competition, companies do not only focus on company profits, but also focus on human resources in company management. This study aims to examine the effect of Transformational Leadership Style on Organizational Commitment, test the effect of Transformational Leadership Style on Employee Performance and examine the effect of Transformational Leadership Style on Employee Engagement at PT PLN (Persero) UP3 Bukittinggi. The samples used according to these characteristics were 53 samples which were in accordance with the acceptable samples for parametric analysis (30<x<500). Transformational Leadership Style has an effect on Organizational Commitment, Transformational Leadership Style has an effect on Employee Engagement and Transformational Leadership Style has an effect on Employee Performance.